"Business is business": a journey into a French suburban drug-dealing bureaucratic gang. Issue 3 (3rd June 2020) - Sorreda, Thomas; Philippe, Xavier
Abstract : Purpose: Illegal companies remain an underexplored research avenue. Indeed, although extant literature has already discussed organizational analysis of illicit businesses from a marketing or an entrepreneurial point of view, few papers have focused on it. The purpose of this study is to explore and uncover the bureaucratic aspects of this kind of structure. To do so, this study intends to demonstrate that even the most hidden organizations in a given society are shaped by common representations orienting them toward well-disseminated models. Design/methodology/approach: An ethno-sociological study was conducted, thanks to a long non-participant immersion (over one year) by observing a drug-dealing organization in a French suburban area located near Paris. Findings: This study illustrates that illicit organizations reproduce traditional organizational schemes that help them to ensure efficiency and sustainability. Indeed, they fit into modern bureaucratic models within which procedures remain highly normative and formal, but also within which interactions between members are both constrained by a regulative framework and, at the same time, enable a certain amount of autonomy and creativity at work. Social implications: The business case in this study analyzes the implications of seeing illicit businesses as organizations like any others. The counterintuitive results show that these organizations set and normalize processes allowing the establishment of a formal hierarchy, and specific yet strict rules. Originality/value: The originality of this paper comes from its unit of analysis and specific subject.